2015
DOI: 10.1007/s13105-015-0424-x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products induce apoptosis in podocytes through induction of endoplasmic reticulum stress

Abstract: Although podocyte apoptosis has been shown to be induced by the accumulation of advanced oxidation protein products (AOPPs), the mechanisms through which AOPPs trigger apoptosis in these cells remain unclear. In this study, we investigated the role of endoplasmic reticulum (ER) stress in AOPP-induced podocyte apoptosis. AOPP treatment induced overexpression of glucose-regulated protein 78 and CCAAT/enhancer-binding protein-homologous protein (CHOP) in podocytes, indicating that AOPPs induced ER stress. Notably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Increasing evidence suggest that ER stress contribute to glomerular and tubular cell injury in kidney diseases [ 19–21 ]. In response to ER stress, three UPR signal transduction pathways are initiated by three transmembrane proteins: protein kinase-like ER kinase (PERK), activating transcription factor 6 (ATF6), and inositol requiring 1 (IRE1) [ 22 ]. The subsequence of activation of PERK is to cause the phosphorylation of eukaryotic translation initiation factor (eIF)-2α, which further causes the down-regulation of translation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggest that ER stress contribute to glomerular and tubular cell injury in kidney diseases [ 19–21 ]. In response to ER stress, three UPR signal transduction pathways are initiated by three transmembrane proteins: protein kinase-like ER kinase (PERK), activating transcription factor 6 (ATF6), and inositol requiring 1 (IRE1) [ 22 ]. The subsequence of activation of PERK is to cause the phosphorylation of eukaryotic translation initiation factor (eIF)-2α, which further causes the down-regulation of translation.…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of misfolded/unfolded proteins in the ER and alterations in calcium homeostasis lead to ER stress, which leads to the unfolded protein response (UPR, a series of integrative stress pathways). ER stress has been widely demonstrated to contribute to both glomerular and tubular cell injuries in kidney diseases [ 19–21 ]; moreover, it has been shown to be a mediator of podocyte apoptosis [ 22–25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have indicated that AGEs can also adversely affect endoplasmic reticulum function, leading to pathogenic endoplasmic reticulum stress (38)(39)(40)(41). Inhibitors of advanced glycation acting as potent endoplasmic reticulum stress modulators with beneficial effects in restoring endoplasmic reticulum homeostasis and adjusting the physiological unfolded protein response level, present an emerging therapeutic approach with significant applications, particularly in the context of metabolic dysfunction (42).…”
Section: Discussionmentioning
confidence: 99%
“…It could induce glomerular obstacle of podocyte structure and function, participate in a variety of kidney diseases, and also lead to glomerular sclerosis [ 66 ]. Continuous endoplasmic reticulum stress had effects on the function of endoplasmic reticulum and could launch apoptosis signaling pathways which were mediated by endoplasmic reticulum stress at the same time and then activated the downstream apoptotic signaling molecules [ 67 ]. In patients with diabetes, hyperglycemia can motivate endoplasmic reticulum stress through a variety of ways, then cause cellular damage [ 68 ].…”
Section: Main Signaling Pathways Of Podocyte Injury Mechanism In Dmentioning
confidence: 99%